2021
DOI: 10.21203/rs.3.rs-805962/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Swab test in biological fluids as predictor of COVID-19 transmission risk during surgery: A prospective cross-sectional study from an Italian COVID center

Abstract: Background. The contamination of body fluids by Severe Acute Respiratory Syndrome Coronavirus 2 during surgery is current matter of debate in the scientific literature concerning CoronaVIrus Disease 2019. Surgical guidelines were published during the first wave of the COVID-19 pandemic and recommended to avoid laparoscopic surgery as much as possible, in fear that the chimney effect of high flow intraperitoneal gas escape during, and after, the procedure would increase the risk of viral transmission.Aim. The a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…None of the surgical equipment samples for this study had tested positive (other than ETT, nasal probe), whereas, in our previous study, 2 of 11 samples from surgical equipment (scissors, clamps) had tested positive 14 . These low sample positivity rates align with findings of a study by Fabbri et.al that indicate that the transmission risk during surgery, specifically through aerosolization from the surgical field, is low 39 .…”
Section: Discussionsupporting
confidence: 89%
“…None of the surgical equipment samples for this study had tested positive (other than ETT, nasal probe), whereas, in our previous study, 2 of 11 samples from surgical equipment (scissors, clamps) had tested positive 14 . These low sample positivity rates align with findings of a study by Fabbri et.al that indicate that the transmission risk during surgery, specifically through aerosolization from the surgical field, is low 39 .…”
Section: Discussionsupporting
confidence: 89%
“…15,16,34 Regardless, this should not be assumed as the rule as there have been other reports suggesting negative results in similar settings as well. 35,36 Agnes et al 37 reported a case similar to ours, where ascitic fluid was negative in a patient with a duodenal perforation, which may suggest that the virus be shed in the distal gastrointestinal tract by mechanisms not fully understood.…”
Section: Discussionsupporting
confidence: 67%
“…Our last hypothesis is that the virus could not be always present. In a recent article, we hypothesized that the possible presence of SARS-CoV-2 in the peritoneum may depend on the disease stage and the associated cytokine storm [ 31 ]. In the severe form of COVID-19, the hyperinflammation, manifesting with cytokine storming, can lead to a greater viremic spread and, in such cases, it is possible that the virus would cross the pleural/peritoneal membrane.…”
Section: Discussionmentioning
confidence: 99%